Little Robin Redbreast : a Mother Goose rhyme - Halpern, Shari (New York : North-South Books, 1994)
An illustrated version of the traditional rhyme describing a robin's encounter with a cat.
School Library Journal
Booklist
Publisher's Weekly
1.6
K-3
Keywords: Nursery rhymes; Children's poetry; Nursery rhymes; Nursery rhymes